2022
DOI: 10.3390/ijerph192114611
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Frequency and Health-Related Quality of Life in Spanish Children and Adolescents with Asthma: A Cross-Sectional Study

Abstract: Asthma is considered the most prevalent chronic childhood disease worldwide. Physical activity (PA) represents a tool to improve patients with respiratory diseases’ health-related quality of life (HRQoL). A cross-sectional study examining data from the Spanish National Health Survey (ENSE 2017) was carried out to investigate the associations between the PAF (physical activity frequency) and health-related quality of life (HRQoL) in asthmatic children and adolescents from 8 to 14 years old (total 11.29 years ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Several studies have shown that an increase in PA improves quality of life in patients with asthma [40]. One of the reasons that could justify this association is that PA reduces the likelihood of asthma symptoms owing to cardiorespiratory adjustment to exercise, a decrease in BMI, improved self-esteem and mood, and less frequent symptoms of anxiety and depression [41]. In fact, PA and self-rated health have been shown to be related to good mental health in patients with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that an increase in PA improves quality of life in patients with asthma [40]. One of the reasons that could justify this association is that PA reduces the likelihood of asthma symptoms owing to cardiorespiratory adjustment to exercise, a decrease in BMI, improved self-esteem and mood, and less frequent symptoms of anxiety and depression [41]. In fact, PA and self-rated health have been shown to be related to good mental health in patients with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Every year 3.7 million people die because of air pollution, e.g., due to an increased quantity of ultrafine particles deposition, as well as air pollution exposure and cardiovascular disease [9,10]. Environmental quality and landscape diversity are important assets for public health and physical activity [9][10][11][12]. The degradation of green areas has also created pressure on air quality.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation system of “production, living and ecological” environmental quality in cities is the basis for the balanced development of “production, living and ecological” environment. A large number of studies have been conducted and many important research results have been achieved, including a series of studies on the quality of production environment and its influencing factors [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], a series of studies on the quality of life and its influencing factors [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], and a series of studies on water, soil and gas pollution and related environmental pollution [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%